A review of best practices for effective coaching - Zainal Abiddin, Norhasni; Idris, Khairuddin (Department of History Education, Indonesia University of Education, 2008)
Coaching is a part of educational training to develop people in the professions, with the aim to achieve some goal or develop specific skills. It is related to self development, professional growth and career development of the coachee. Through the process of coaching, coachees deepen their learning, improve their performance, and enhance their quality of life. Coaching is, in essence, about human relationships, between the coach and coachee, and the coach and the organization. Not only do coaches have to play their role but the coachees too, and all this must be placed within the specific institutional context. The coaching relationship has been described as learning activity for beginners as well as experienced practitioners such as teachers, administrators, managers, and other professionals. It concentrates on where we are now and what we are willing to do to get where we want to be in the future, recognizing that results are a matter of our intentions, choices and actions. Generally, coaching is derived from sport. Recent practices in coaching in non-sporting environments focus on helping clients to analyze and solve their own challenges, rather than offering advice or direction. This article is designed to summarize existing literature on coaching in order to assist coaches-coachees in enhancing the best practices for effective coaching. Thus, this article focuses on two major areas: the concept of coaching and its theoretical foundations; and the nature of the coach-coachee relationship.